EFFECTIVENESS OF SERVQUAL DIMENSIONS IN INCREASING CUSTOMER SATISFACTION BETWEEN HOTEL AND RESORT IN MELAKA - Raja Abd. Rahman, Raja Roslan; Husein, Khalthom; Adnan, Hassan; Ahmad Ridzuan, Ahmad Hidayat; Saari, Juan Riza (Journal of Human Capital Development (JHCD), 2010)
The role of service quality in the success of hotel businesses cannot be denied. It is vital for the hotel managers to have a good understanding on what exactly the customers want. Furthermore there also had been concerns that service quality dimensions may differ from one country to another. Hence this study intends to analyze the service quality dimensions in increasing customer satisfaction by conducting comparative study between three star hotels and resorts in Melaka, Malaysia to identify which service quality dimensions are significant in both type of establishment, to identify whether there are any differences regarding the perceived dimensions and to find out which dimensions are the best predictor of overall service quality. Probability sampling techniques were used to collect data from the modified SERVQUAL instruments. SPSS 16.0 for Windows was employed for the data analysis. Descriptive analysis such as means, standard deviation and frequencies are calculated. Reliability issues are tested and dimensionality of the scale is confirmed through an exploratory factor analysis. Finally, regression models were developed and analyzed for both type of establishments. Factor analysis confirmed the five-dimensional structure of SERVQUAL both in hotel and resort category; however, some of the dimensions found and their components were different from the original SERVQUAL. Results of regression analysis revealed that four dimensions were significant in determining overall service quality in hotel category while only one dimension were significant in determining overall service quality in resort category. The study concluded that identifying the perceptions of customers, the dimensions of service quality, and their relative importance for customers for each specific segment of the hotel industry would definitely help managers in the challenge of increasing customer satisfaction between Hotel and Resort in Melaka. Keywords: effectiveness, SERVQUAL dimensions, increasing, customer satisfaction